A fe single-atom catalyst for activation of persulfate and a preparation method and application thereof

CN122875271APending Publication Date: 2026-10-09湖南工商大学
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611069550.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-17
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]有鉴于此,本发明的目的在于提出一种过硫酸盐活化用Fe单原子催化剂及其制备方法和应用,以解决现有铁基催化剂在活化过硫酸盐降解三氯卡班时,存在铁原子利用率低、活性位点易团聚失活、载体传质效率不足以及对顽固污染物矿化能力有限的问题

Benefits of technology

本发明提供的技术方案,通过内嵌含氧前驱位点、外置挥发性刻蚀剂的时序与空间控制策略,成功构建了一维中空薄壁且富含氮氧掺杂的碳氮载体。该载体不仅具有开放的多级孔道结构,显著增大了比表面积,为反应物提供了高效的传质路径,而且其内部预置的含氧缺陷位点为后续铁物种的锚定提供了高密度的、强结合的“着陆点”,从载体结构层面为高分散活性中心的形成奠定了基础。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875271A_ABST
    Figure CN122875271A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of catalysts, in particular to a Fe single-atom catalyst for activating persulfate, a preparation method and application thereof. The preparation method comprises the following steps: assembling melamine, cyanuric acid and oxalic acid dihydrate in a wet state to form a rod-shaped precursor; spraying an ammonium chloride solution outside and drying; performing two-stage heat treatment to obtain a one-dimensional hollow nitrogen-rich oxygen-doped carbon-nitrogen carrier; dispersing the carrier, adding 1,10-phenanthroline monohydrate first, then adding a ferric triacetylacetone solution, performing vacuum-assisted infiltration, evaporating dry, and performing heat treatment, and then performing acid pickling and drying to obtain the catalyst. Through the strategy of step-by-step construction of the carrier structure and post-embedding of iron species, the agglomeration of iron atoms is effectively inhibited, and stable mixed coordination active centers are formed. When the obtained catalyst is used for activating persulfate to degrade organic pollutants such as trichlorocarban, the catalyst shows high activity, wide pH adaptability, good actual water adaptability and cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, and in particular to a Fe single-atom catalyst for persulfate activation, its preparation method, and its application. Background Technology

[0002] With the acceleration of industrialization and urbanization, emerging organic pollutants such as pharmaceuticals, personal care products, and endocrine disruptors are frequently detected in aquatic environments, posing a potential threat to aquatic ecological security and human health. Substances like the antibacterial agent triclocarban are chemically stable and difficult to remove effectively by traditional water treatment processes, making the development of efficient and stable advanced oxidation technologies urgent. Technologies based on the activation of persulfate to generate strong oxidizing free radicals show great promise in the treatment of recalcitrant organic wastewater due to their strong oxidizing power and wide pH adaptability. Among these, transition metal-activated persulfate, as an important heterogeneous catalytic pathway, has attracted considerable attention.

[0003] Among transition metals, iron has been extensively studied due to its environmental friendliness, abundant reserves, and variable valence state. Early homogeneous Fenton or Fenton-like technologies directly activated hydrogen peroxide or persulfate using ferrous salts. Although the reaction rate was relatively fast, it suffered from problems such as a narrow pH range, large iron sludge production, and difficulty in reusing the sludge. To address these issues, researchers have developed various heterogeneous iron-based catalysts, such as iron oxides, zero-valent iron, and their composites. However, the iron species in these materials often exist in the form of nanoparticles or clusters, which are prone to leaching and aggregation during catalysis. This results in a limited number of active sites, low atom utilization, and insufficient mineralization capacity for structurally stable and highly hydrophobic pollutants such as triclocarban, making it difficult to achieve deep purification.

[0004] To overcome the aforementioned bottlenecks, single-atom catalysts anchoring iron in an atomically dispersed form on a support have emerged, theoretically achieving 100% atom utilization efficiency and providing the possibility of regulating the local coordination environment of active sites. Carbon-nitrogen materials, rich in nitrogen coordination sites, have become one of the ideal supports for stabilizing iron single atoms. Existing technologies have explored strategies such as co-pyrolysis of iron precursors with carbon-nitrogen precursors to prepare iron single-atom catalysts, demonstrating their potential in activating persulfate. However, in such methods, iron atoms readily migrate and aggregate to form nanoparticles during high-temperature pyrolysis, making it difficult to precisely control the dispersion and coordination structure of iron species. Furthermore, carbon-nitrogen supports prepared by conventional methods are often solid block structures with limited specific surface area and underdeveloped pores, restricting mass transfer of reactants and the full exposure of active sites.

[0005] More importantly, for recalcitrant pollutants like triclocarban, which are highly hydrophobic and exist in molecular form across a wide pH range, relying solely on traditional single-coordination structures such as Fe-N4 often presents limitations in key steps such as pollutant adsorption, electron transfer, and reactive oxygen species generation, leading to low oxidation efficiency and incomplete mineralization. The anti-interference capabilities and long-term operational stability of existing catalysts in complex aquatic matrices (such as surface water containing natural organic matter or wastewater treatment plant effluent containing residual pollutants) still need improvement. Therefore, how to synergistically optimize the microstructure of the carrier (such as pores and morphology) and the electronic structure of the active center (such as the coordination environment) while ensuring high dispersion and stable anchorage of iron species, to simultaneously enhance mass transfer, adsorption, and catalytic oxidation processes, thereby achieving efficient and deep mineralization of stubborn pollutants like triclocarban, while also considering adaptability in practical water treatment scenarios, remains a key challenge in this technological field. Summary of the Invention

[0006] In view of this, the purpose of this invention is to propose a Fe single-atom catalyst for persulfate activation, its preparation method and application, in order to solve the problems of low iron atom utilization, easy aggregation and deactivation of active sites, insufficient mass transfer efficiency of the support and limited mineralization ability of stubborn pollutants in the activation of persulfate degradation of triclocarban by existing iron-based catalysts.

[0007] To achieve the above objectives, the present invention provides a method for preparing a Fe single-atom catalyst for persulfate activation, comprising the following steps: S1. Mix melamine aqueous solution with cyanuric acid aqueous suspension, then add oxalic acid dihydrate aqueous solution, perform wet supramolecular assembly, age and stand, filter and wash to obtain rod-shaped supramolecular precursor wet filter cake. S2. Spray the ammonium chloride aqueous solution onto the surface of the wet filter cake in several stages, and stir after each spraying to distribute the ammonium chloride on the outer layer of the wet filter cake. Then dry to obtain a solid precursor with ammonium chloride loaded on the outer layer. S3. The solid precursor is subjected to two-stage heat treatment under a nitrogen atmosphere to obtain a one-dimensional hollow nitrogen-oxygen-rich doped carbon-nitrogen support. S4. The carrier is dispersed in anhydrous ethanol, 1,10-phenanthroline monohydrate is added first, followed by anhydrous ethanol solution of iron triacetylacetone. After the addition is completed, vacuum-assisted impregnation is performed, the solvent is evaporated and dried to obtain the intermediate product with iron precursor embedded later. S5. The intermediate product is subjected to a second heat treatment under a nitrogen atmosphere, followed by acid washing with hydrochloric acid, filtration, water washing and drying to obtain a Fe single-atom catalyst for persulfate activation.

[0008] Preferably, the mass ratio of melamine, cyanuric acid, oxalic acid dihydrate and ammonium chloride is 10-14:9-13:4-8:12-24.

[0009] Preferably, in step S1, the temperature for wet supramolecular assembly is 70-85℃ and the time is 1-3h; the temperature for aging is 55-65℃ and the time is 3-6h; and the time for settling is 10-14h.

[0010] Preferably, in step S2, the ammonium chloride aqueous solution is prepared by mixing ammonium chloride and deionized water at a ratio of 12-24g:30-60mL.

[0011] Preferably, in step S2, the number of spraying times is 3-5, and the mixture is stirred for 1-3 minutes after each spraying; the drying temperature is 55-70℃, and the drying time is 6-10 hours.

[0012] Preferably, in step S3, the two-stage heat treatment includes: heating to 260-300℃ at 2-3℃ / min under a nitrogen atmosphere and holding for 1-2 hours, and then heating to 520-560℃ at 2-4℃ / min and holding for 2-3 hours.

[0013] Preferably, in step S4, the amount of 1,10-phenanthroline monohydrate is 0.12-0.16 parts by weight, and the amount of iron triacetylacetone is 0.015-0.045 parts by weight, based on 1 part by weight of the carrier.

[0014] Preferably, in step S4, the vacuum-assisted impregnation is performed three times, each time evacuated to an absolute pressure of 20-30 kPa and maintained for 8-15 minutes, and then restored to normal pressure; after the vacuum-assisted impregnation, stirring is continued at 35-45°C for 4-8 hours.

[0015] Preferably, in step S5, the secondary heat treatment involves heating to 480-520°C at a rate of 2-3°C / min under a nitrogen atmosphere and holding at that temperature for 1-2 hours.

[0016] Furthermore, the present invention also provides a Fe single-atom catalyst for persulfate activation, comprising a one-dimensional hollow nitrogen- and oxygen-rich doped carbon-nitrogen support and Fe single-atom active sites anchored on the support.

[0017] Furthermore, the present invention also provides an application of a Fe single-atom catalyst for persulfate activation, used to activate persulfate to degrade organic pollutants; the organic pollutant being triclocarban.

[0018] The beneficial effects of this invention are: The technical solution provided by this invention successfully constructs a one-dimensional hollow thin-walled carbon-nitrogen support rich in nitrogen and oxygen doping through a timing and spatial control strategy of embedding oxygen-containing precursor sites and externally placing volatile etchants. This support not only has an open hierarchical porous structure, significantly increasing the specific surface area and providing an efficient mass transfer pathway for reactants, but also its internally pre-placed oxygen-containing defect sites provide high-density, strongly bound "landing points" for the subsequent anchoring of iron species, laying the foundation for the formation of highly dispersed active centers at the support structural level.

[0019] By employing a stepwise post-intercalation strategy of "first constructing an iron-free carbon-nitrogen framework, then introducing an iron precursor," the migration and aggregation of iron species during high-temperature carbonization are effectively avoided. This approach allows iron atoms to be precisely anchored at established, stable nitrogen- and oxygen-rich defect sites, significantly suppressing the formation of iron nanoparticles. This, in turn, significantly improves the utilization efficiency of iron atoms, reduces the risk of dissolution and loss of active components during the reaction, and enhances the inherent stability of the catalyst.

[0020] Furthermore, by employing a sequential design of "first adsorption and localization of nitrogen-containing ligands, followed by vacuum-assisted introduction of organic iron sources," a stable Fe-N / O mixed coordination environment can be formed between iron atoms and nitrogen and oxygen atoms in the support. Compared to single Fe-N coordination, this unique coordination structure is more conducive to optimizing the adsorption and activation process of persulfate molecules at active sites, promoting rapid transfer of interfacial electrons, and potentially regulating the generation pathway of high-valence iron-oxygen species. This synergistically enhances the oxidative attack capability and deep mineralization potential against hydrophobic and recalcitrant organic pollutants such as triclocarban.

[0021] In summary, this approach integrates innovation across three levels: carrier structure design, active center construction strategy, and coordination environment regulation. This results in a catalyst that exhibits high activity and high atom utilization, while maintaining excellent catalytic performance and recycling stability over a wide pH range and in surface water and secondary effluent containing complex matrices. This provides a superior catalyst option for the application of persulfate advanced oxidation technology in practical water treatment. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in this invention or the prior art, the accompanying drawings used in the description of the embodiments or the prior art will be briefly introduced below.

[0023] Figure 1 This is a high-resolution atomic image of the Fe single-atom catalyst for persulfate activation prepared in Example 1 of the present invention under aberration-corrected transmission electron microscope (HAADF) mode. Figure 2The graphs show the triclocarban removal efficiency of the catalyst prepared in Example 1 of this invention, the catalysts prepared in Comparative Examples 1-6, the blank group, and the adsorption group. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments.

[0025] Example 1: Step 1: Add 12g of melamine to 400mL of 80℃ deionized water and stir until a clear solution is formed. Add 11g of cyanuric acid to 200mL of 80℃ deionized water and stir to form a uniform suspension. Slowly add the cyanuric acid suspension to the melamine solution. Then dissolve 6g of oxalic acid dihydrate in 120mL of deionized water and add it all at once. Stir continuously at 80℃ for 2 hours, then age at 60℃ for 4 hours, and then let stand for 12 hours to obtain rod-shaped supramolecular precursor slurry. Then filter and wash the filter cake with 100mL of deionized water and 100mL of anhydrous ethanol in sequence. Step 2: Spread the wet filter cake obtained in Step 1 in a glass dish, dissolve 18g of ammonium chloride in 40mL of 60℃ deionized water to prepare an ammonium chloride solution; spray the solution onto the surface of the filter cake in 4 portions, 10mL each time, and stir with a glass rod for 2min after each spraying, and then dry at 60℃ for 8h to obtain a solid precursor with ammonium chloride loaded on the outer layer; Step 3: Transfer the solid precursor obtained in Step 2 to a covered alumina crucible, heat it to 280℃ at 2℃ / min under a nitrogen atmosphere and hold it for 1h, then heat it to 540℃ at 3℃ / min and hold it for 2h. After natural cooling, take it out, grind it gently and pass it through a 100-mesh sieve to obtain a one-dimensional hollow nitrogen-oxygen-rich doped carbon-nitrogen support. Step 4: Add 1g of the carrier obtained in Step 3 to 120mL of anhydrous ethanol, sonicate for 30min, then add 120mg of 1,10-phenanthroline monohydrate and stir at 40℃ for 2h; separately dissolve 25mg of iron triacetylacetone in 30mL of anhydrous ethanol to prepare an iron precursor solution, and then add the iron precursor solution dropwise to the carrier dispersion over 30min; after the dropwise addition is completed, perform vacuum-assisted impregnation 3 times, each time drawing to 20kPa absolute pressure and holding for 10min, then restoring to normal pressure, then continue stirring at 40℃ for 6h, then evaporate the solvent at 80℃ and dry for 6h to obtain the intermediate product with iron precursor embedded in it; Step 5: The intermediate product obtained in Step 4 is heated to 500℃ at 2℃ / min under a nitrogen atmosphere and kept at that temperature for 1h. After natural cooling, it is added to an acid washing solution prepared with 8mL hydrochloric acid and 192mL deionized water. The mixture is stirred at room temperature for 2h, then filtered and washed with deionized water until the pH of the filtrate is 6 to 7. The filtrate is then dried at 80℃ for 12h to obtain the Fe single-atom catalyst for persulfate activation.

[0026] Example 2: The difference from Example 1 is that: 10g melamine, 9g cyanuric acid, 4g oxalic acid dihydrate, 12g ammonium chloride, 80mg 1,10-phenanthroline monohydrate, and 15mg iron triacetylacetone were used; the first heat treatment was 270℃ for 1 hour, the second heat treatment was 530℃ for 2 hours, and the second heat treatment was 480℃ for 1 hour; the remaining conditions were the same as in Example 1.

[0027] Example 3: The difference from Example 1 is that: 14g melamine, 13g cyanuric acid, 8g oxalic acid dihydrate, 24g ammonium chloride, 160mg 1,10-phenanthroline monohydrate, and 45mg iron triacetylacetone were used; the first heat treatment was held at 300℃ for 2 hours, the second heat treatment was held at 560℃ for 3 hours, and the second heat treatment was held at 520℃ for 2 hours; the remaining conditions were the same as in Example 1.

[0028] Example 4: The difference from Example 1 is that: 12g melamine, 12g cyanuric acid, 7g oxalic acid dihydrate, 15g ammonium chloride, 140mg 1,10-phenanthroline monohydrate, and 35mg ferric triacetylacetone were used; the first heat treatment was held at 280℃ for 1 hour, the second heat treatment was held at 550℃ for 2 hours, and the final heat treatment was held at 510℃ for 1 hour. This example is used for the stable protection of the intermediate window.

[0029] Comparative Example 1: The difference from Example 1 is that 6g of oxalic acid dihydrate is not added in step 1, and 120mL of deionized water is used instead of the original 120mL of deionized water used to dissolve the oxalic acid dihydrate; the other conditions are the same as in Example 1.

[0030] Comparative Example 2: The difference from Example 1 is that: in step 2, 18g of ammonium chloride is not added, and 40mL of deionized water at 60℃ is used instead of ammonium chloride solution to spray the wet filter cake obtained in step 1 in 4 times, with 10mL sprayed each time, and the mixture is stirred for 2 minutes after each spray; the other conditions are the same as in Example 1.

[0031] Comparative Example 3: The difference from Example 1 is as follows: In step 1, after adding 6g of oxalic acid dihydrate and stirring continuously at 80°C for 30min, 18g of ammonium chloride was dissolved in 40mL of deionized water at 60°C and added to the mixture at once, and stirring was continued at 80°C until the end of step 1; in step 2, the ammonium chloride solution was no longer sprayed, and the wet filter cake obtained in step 1 was dried at 60°C for 8h; the other conditions were the same as in Example 1.

[0032] Comparative Example 4: The difference from Example 1 is as follows: Before proceeding to step 2, 120 mg of 1,10-phenanthroline monohydrate and 25 mg of iron triacetylacetone monohydrate were dissolved in 15 mL of anhydrous ethanol. The mixture was then sprayed evenly onto the surface of the wet filter cake and stirred for 2 min. Steps 2 and 3 were then performed as in Example 1. In step 4, 1,10-phenanthroline monohydrate and iron triacetylacetone monohydrate were not added. Instead, the carrier obtained in step 3 was added to 120 mL of anhydrous ethanol, ultrasonically dispersed for 30 min, and then subjected to three vacuum-assisted impregnation cycles. Each cycle was evaporated to an absolute pressure of 20 kPa and maintained for 10 min. The pressure was then restored to normal, and the mixture was stirred at 40 °C for 6 h. Finally, the solvent was evaporated at 80 °C and the mixture was dried for 6 h. Step 5 was the same as in Example 1.

[0033] Comparative Example 5: The difference from Example 1 is that 120 mg of 1,10-phenanthroline monohydrate is not added in step 4. First, 1 g of the carrier obtained in step 3 is added to 120 mL of anhydrous ethanol and ultrasonically dispersed for 30 min. Then, it is stirred at 40 °C for 2 h. Then, a solution of 25 mg of iron triacetylacetone dissolved in 30 mL of anhydrous ethanol is added dropwise to the dispersion within 30 min. The other conditions are the same as in Example 1.

[0034] Comparative Example 6: The difference from Example 1 is that in step 4, 25 mg of iron triacetylacetone is first dissolved in 30 mL of anhydrous ethanol to prepare a solution, and then added dropwise to the dispersion formed by 1 g of the carrier obtained in step 3 and 120 mL of anhydrous ethanol within 30 min. After stirring at 40 °C for 2 h, 120 mg of 1,10-phenanthroline monohydrate is added and stirring is continued for 2 h; the other conditions are the same as in Example 1.

[0035] Performance testing: General testing principles: Unless otherwise specified, all triclocarban removal tests were conducted in a 500 mL amber glass reactor with a reaction volume of 250 mL. The catalyst dosage was 0.20 g / L, and the active component in the potassium persulfate complex salt was 0.50 mmol / L (calculated as persulfate). The reaction temperature was 25 ± 1 °C, the magnetic stirring speed was 600 r / min, and the initial pH was adjusted to 7.00 ± 0.05. The reaction was allowed to equilibrate in the dark for 30 min before adding the potassium persulfate complex salt to initiate the reaction, which was recorded as 0 min. The triclocarban stock solution was prepared with a mass concentration of 1.00 g / L, using acetonitrile as the solvent. The initial concentration of triclocarban used for removal efficiency and rate testing was set at 0.50 mg / L. The preparation method was as follows: accurately transfer 0.50 mL of triclocarban stock solution into a clean beaker, allow acetonitrile to evaporate naturally at 25 °C until no visible droplets remain, add 200 mL of primary water and stir for 12 h, then transfer to a 1 L volumetric flask and make up to volume.

[0036] Sample morphology characterization: The catalyst prepared in Example 1 was characterized using aberration-corrected transmission electron microscopy in HAADF mode. The results are as follows: Figure 1 As shown.

[0037] Specific surface area and pore structure tests: 100 mg of each sample was weighed and placed in a sample tube. The sample was degassed under vacuum at 120 °C for 6 h. After cooling to room temperature, nitrogen adsorption-desorption tests were performed. The liquid nitrogen temperature was maintained at 77 K, and the relative pressure range was set to 0.01–0.99. Specific surface area, total pore volume, and average pore size were calculated based on the adsorption data. The results are shown in Table 1.

[0038] Total iron content test: The total iron content of the samples was determined according to GB / T 39486-2020. For the total iron content test, 10.0 mg of each sample was accurately weighed and placed in a polytetrafluoroethylene digestion vessel. 6.0 mL of nitric acid and 2.0 mL of hydrochloric acid were added, and the mixture was digested at 180 °C for 30 min. After cooling, the mixture was transferred to a 50.0 mL volumetric flask and brought to a final volume. The total iron mass fraction was determined by inductively coupled plasma mass spectrometry. The results are shown in Table 1.

[0039] Triclocarban removal efficiency and apparent first-order rate constant testing: Triclocarban concentration was determined by high-performance liquid chromatography (HPLC), and the quantitative method was performed according to GB / T 34856-2017. Peak identification of representative samples was verified using liquid chromatography-mass spectrometry (LC-MS) according to GB / Z35959-2018. HPLC conditions were set as follows: C18 column, 250 mm × 4.6 mm, 5 μm; mobile phase: methanol and water, v / v ratio 75:25; flow rate: 1.0 mL / min; column temperature: 30 ℃; detection wavelength: 264 nm; injection volume: 10 μL. Standard curve concentration points were set at 0.01 mg / L, 0.05 mg / L, 0.10 mg / L, 0.20 mg / L, 0.50 mg / L, and 1.00 mg / L. After the reaction started, 5.00 mL samples were taken at 0 min, 1 min, 2 min, 5 min, 10 min, 15 min, 20 min, and 30 min, respectively. The reaction was immediately terminated by adding 0.10 mL of 10 g / L sodium thiosulfate solution. The samples were then filtered through a 0.22 μm filter membrane before analysis. A blank control group without catalyst and an adsorption group without potassium persulfate composite salt were simultaneously set up to distinguish between contributions from simple oxidation and simple adsorption. The results are as follows: Figure 2 As shown; data from 0-15 minutes were processed using ln(C0 / C). t )=k t Linear fitting was performed to obtain the apparent first-order rate constant k, and the results are shown in Table 1.

[0040] Initial pH and actual water sample adaptability test: The initial pH was adjusted and measured according to HJ 1147-2020. The collection, preservation and management of surface water samples and secondary effluent samples were performed according to HJ 91.2-2022, HJ 91.1-2019, HJ 494-2009, HJ495-2009 and HJ 493-2009, respectively. The initial pH adaptability test was set up with three groups of pH values ​​of 5.00±0.05, 7.00±0.05 and 9.00±0.05. The reaction conditions were the same as those for the triclocarban removal efficiency and apparent first-order rate constant test. The triclocarban removal rate was measured after 30 min. In the actual water sample adaptability test, surface water samples were taken from the surface layer of urban rivers at 0.5m, and secondary effluent samples were taken from the effluent outlet of the secondary sedimentation tank of the municipal sewage treatment plant. Both samples were stored at 4℃ after sampling and used within 24 hours. Before use, the samples were filtered through a 0.45μm filter membrane, and the initial concentration of triclocarban was uniformly spiked to 0.50mg / L. The reaction was then carried out, and the triclocarban removal rate was recorded after 30 minutes. The results are shown in Table 1.

[0041] Cyclic stability test: Cyclic stability was tested under the conditions of triclocarban removal efficiency and apparent first-order rate constant. After each reaction of 30 min, the catalyst was separated by centrifugation at 8000 r / min for 5 min, washed three times with primary water and once with anhydrous ethanol, and dried at 80℃ for 6 h before being used for the next cycle. This was repeated for 5 cycles. The triclocarban removal rate was measured for 30 min in each cycle. The results are shown in Table 1.

[0042] Table 1 Performance Test Results

[0043] Data Analysis: As can be seen from the data in Table 1, the iron single-atom catalyst for persulfate activation prepared in this invention achieves a good balance between specific surface area, pore structure, iron loading retention rate, adaptability to different initial pH levels, adaptability to actual water samples, and cycle stability. This may be because oxalate dihydrate first enters the precursor during the wet supramolecular assembly stage, pre-forming oxygen-containing sites conducive to iron stable anchoring; ammonium chloride is then distributed on the outer layer after the formation of the rod-shaped precursor, making it easier to form thin-walled hollow structures and interconnected channels during heat treatment, thus balancing reactant enrichment and diffusion; based on this, the addition of 1,10-phenanthroline monohydrate followed by iron(III) triacetylacetone, combined with vacuum-assisted embedding, helps iron enter the vicinity of nitrogen- and oxygen-rich sites in a more dispersed state, forming a more stable co-coordination environment of iron with nitrogen and oxygen, thereby promoting the activation of potassium persulfate monohydrate complex salt, interfacial electron transfer, and the generation of high-valence iron-oxygen species. Therefore, it can balance rapid removal, adaptability to complex water bodies, and stability for repeated use.

[0044] As can be seen from the data in Example 1 and Comparative Example 1 in Table 1, even without the addition of oxalic acid dihydrate, the material can still form a certain porous structure, but the total iron content, removal rate, adaptability to actual water samples, and retention after circulation all decrease simultaneously. The main reason is that the precursor lacks pre-placed oxygen-containing sites, and subsequent iron species rely more on adsorption at surface nitrogen sites or defect edges, resulting in insufficient anchoring strength and difficulty in fully forming a stable environment for iron, nitrogen, and oxygen coordination. Therefore, internal oxygen-containing sites are not simply for oxygenation, but are a key prerequisite for determining subsequent post-intercalation efficiency and single-atom stability; this role cannot be replaced by external pore formation alone.

[0045] As can be seen from the data in Table 1 for Example 1 and Comparative Example 2, without the addition of ammonium chloride, the pore volume, pore openness, and removal performance under neutral conditions are significantly limited, especially in actual water samples and after recycling. The main reason for this is likely the lack of a volatilization etching process in the outer layer, the thicker carrier wall, and the longer mass transfer path, making it difficult for the triclocarban and potassium persulfate composite salt to fully contact the internal active sites. This indicates that thinning the outer wall and constructing interconnected pores have a significant amplifying effect on the internal anchoring points; only the combination of both demonstrates a superior effect compared to either improvement alone.

[0046] As can be seen from the data in Table 1 for Example 1 and Comparative Example 3, the overall performance of the material further decreased after mixing and adding oxalic acid dihydrate and ammonium chloride during the precursor slurry stage and omitting the subsequent outer layer coating. This indicates that although both components participate in structure regulation, their positions and timing of action are not interchangeable. When ammonium chloride enters the assembly system prematurely, it easily interferes with the orderly formation of rod-shaped supramolecular structures, and oxalic acid dihydrate also struggles to maintain its internal directional distribution, ultimately resulting in insufficient internal anchoring points and insufficient external etching channels. Therefore, the sequential control of this invention produces an unexpected synergistic effect, demonstrating a comprehensive improvement greater than the sum of its parts (1+1>2), rather than simply using two additives together.

[0047] As can be seen from the data in Table 1 for Example 1 and Comparative Example 4, the catalytic performance and stability were relatively low after 1,10-phenanthroline monohydrate and iron triacetylacetone were pre-sprayed onto the wet filter cake and subjected to the first high-temperature framework formation process. This is because the iron species enter the polymerization and thermal condensation stages too early, making them more prone to local enrichment, nucleation and growth, and subsequent acid leaching, thus making it difficult to retain sufficient atomic-level dispersion sites. This indicates that pre-forming the framework and then embedding iron is not a routine process adjustment, but rather a key step to inhibit iron aggregation and improve iron atom utilization.

[0048] As can be seen from the data in Table 1 for Examples 1, 5, and 6, even with the hollow nitrogen-rich oxygen-doped carbon-nitrogen support remaining unchanged, the presence or absence of 1,10-phenanthroline monohydrate and its order of addition with iron triacetylacetone significantly affect the removal rate, alkalinity adaptability, and cycle retention. Without 1,10-phenanthroline monohydrate, the iron sites exhibit local coordination unsaturation; when iron is added first followed by 1,10-phenanthroline monohydrate, the adsorbed iron species are difficult to uniformly reorganize. This indicates a clear synergistic effect between ligand pre-positioning and subsequent iron precursor introduction, resulting in a synergistic effect greater than the sum of its parts (1+1>2), which cannot be achieved simply by adding ligands or changing the feeding order.

[0049] Figure 1This is a high-resolution atomic image of the catalyst obtained in Example 1 under aberration-corrected transmission electron microscopy (HAADF) mode. Multiple discretely distributed high-brightness atomic-level contrast points can be observed against a relatively dark carbon-based support background. These bright spots are separated from each other, with sizes approaching the single-atom scale, and no obvious continuous bright regions or nanoparticle aggregation features are observed. The magnified view in the lower right corner further shows that each bright spot has a clear, independent, high-contrast signal. Considering the characteristic that higher atomic numbers in HAADF imaging result in higher brightness, the circled bright spots in the image can be attributed to Fe single atoms stably anchored on N / O-rich defect sites. This indicates that the Fe species in the catalyst prepared in Example 1 have high dispersion and mainly exist in single-atom form on the support surface or edge defect regions.

[0050] from Figure 2 It can be seen that, under the same reaction conditions, the removal of triclocarban by each sample gradually increased with the extension of reaction time, but there were significant differences in the degree of increase among different samples. Among them, Example 1 maintained the highest removal level throughout the entire reaction process, and the increase was the fastest in the first 15 minutes, indicating that it has a stronger activation ability for potassium peroxymonosulfate complex salt and makes fuller use of active sites, thus achieving faster oxidative removal of triclocarban; at 30 minutes, the removal rate of Example 1 was close to 100%, which was significantly better than the comparative examples. In contrast, while Comparative Examples 1 and 2 exhibited some removal capacity, their overall removal rate and final removal rate were lower than those of Example 1, indicating that with only partial structural regulation, it is difficult to simultaneously achieve stable iron site anchoring and mass transfer efficiency. Comparative Examples 3 and 4 showed even more significant decreases, suggesting that disrupting the temporal-spatial distribution relationship between oxalate dihydrate and ammonium chloride, or prematurely introducing iron species into the framework formation process, would weaken the catalyst's structural advantages and lead to insufficient utilization of active sites. The results of Comparative Examples 5 and 6 further demonstrate that the introduction of 1,10-phenanthroline monohydrate and its sequence with iron triacetylacetone play a crucial role in constructing a stable and efficient Fe-N / O coordination environment. Furthermore, the blank and adsorption groups show that the removal rate of triclocarban was low without a catalyst or relying solely on adsorption, indicating that the high removal efficiency of the samples in this invention mainly stems from the oxidative degradation caused by catalytic activation of persulfate, rather than a simple adsorption contribution.

[0051] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

Claims

1. A method for preparing a Fe single-atom catalyst for persulfate activation, characterized in that, Includes the following steps: S1. Mix melamine aqueous solution with cyanuric acid aqueous suspension, then add oxalic acid dihydrate aqueous solution, perform wet supramolecular assembly, age and stand, filter and wash to obtain rod-shaped supramolecular precursor wet filter cake. S2. Spray the ammonium chloride aqueous solution onto the surface of the wet filter cake in several stages, and stir after each spraying to distribute the ammonium chloride on the outer layer of the wet filter cake. Then dry to obtain a solid precursor with ammonium chloride loaded on the outer layer. S3. The solid precursor is subjected to two-stage heat treatment under a nitrogen atmosphere to obtain a one-dimensional hollow nitrogen-oxygen-rich doped carbon-nitrogen support. S4. The carrier is dispersed in anhydrous ethanol, 1,10-phenanthroline monohydrate is added first, followed by anhydrous ethanol solution of iron triacetylacetone. After the addition is completed, vacuum-assisted impregnation is performed, the solvent is evaporated and dried to obtain the intermediate product with iron precursor embedded later. S5. The intermediate product is subjected to a second heat treatment under a nitrogen atmosphere, followed by acid washing with hydrochloric acid, filtration, water washing and drying to obtain a Fe single-atom catalyst for persulfate activation. In step S4, based on 1 part by weight of the carrier, the amount of 1,10-phenanthroline monohydrate is 0.12-0.16 parts by weight, and the amount of iron triacetylacetone is 0.015-0.045 parts by weight.

2. The method for preparing the Fe single-atom catalyst for persulfate activation according to claim 1, characterized in that, The mass ratio of melamine, cyanuric acid, oxalic acid dihydrate and ammonium chloride is 10-14:9-13:4-8:12-24.

3. The method for preparing the Fe single-atom catalyst for persulfate activation according to claim 1, characterized in that, In step S1, the wet supramolecular assembly temperature is 70-85℃ and the time is 1-3h; the aging temperature is 55-65℃ and the time is 3-6h; the standing time is 10-14h.

4. The method for preparing the Fe single-atom catalyst for persulfate activation according to claim 1, characterized in that, In step S2, the spraying is performed 3-5 times, and the mixture is stirred for 1-3 minutes after each spraying; the drying temperature is 55-70℃ and the drying time is 6-10 hours.

5. The method for preparing the Fe single-atom catalyst for persulfate activation according to claim 1, characterized in that, In step S3, the two-stage heat treatment includes: heating to 260-300℃ at 2-3℃ / min under a nitrogen atmosphere and holding for 1-2 hours, and then heating to 520-560℃ at 2-4℃ / min and holding for 2-3 hours.

6. The method for preparing the Fe single-atom catalyst for persulfate activation according to claim 1, characterized in that, In step S4, the vacuum-assisted impregnation is performed three times, each time evacuated to an absolute pressure of 20-30 kPa and maintained for 8-15 minutes, and then restored to normal pressure; after the vacuum-assisted impregnation, stirring is continued at 35-45℃ for 4-8 hours.

7. The method for preparing the Fe single-atom catalyst for persulfate activation according to claim 1, characterized in that, In step S5, the secondary heat treatment involves heating to 480-520℃ at a rate of 2-3℃ / min under a nitrogen atmosphere and holding at that temperature for 1-2 hours.

8. A Fe single-atom catalyst for persulfate activation, characterized in that, It is obtained by the preparation method of Fe single-atom catalyst for persulfate activation according to any one of claims 1-7.

9. An application of the Fe single-atom catalyst for persulfate activation according to claim 8, characterized in that, Used to activate persulfate to degrade organic pollutants.

10. The application of the Fe single-atom catalyst for persulfate activation according to claim 9, characterized in that, The organic pollutant is triclocarban.